Paternalism and Urban Reform: An Introduction - Olson, Sherry (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1989)
The papers introduced deal with changes in the condition of women in Canadian cities. These changes were closely associated with movements of charity and urban reform and they might better be regarded as "counter-reforms" that imposed a new social discipline. In age-sex structures presented for Montreal families and institutional "families" in 1861, women can be identified as subjects and instruments of the new social "order."